O34 Variants in BANK1 are associated with lupus nephritis. (23rd March 2020) - Bolin, Karin; Leonard, Dag; Sandling, Johanna K; Alexsson, Andrei; Pucholt, Pascal; Haarhaus, Malena Loberg; Nititham, Joanne; Jönsen, Andreas; Sjöwall, Christopher; Bengtsson, Anders A; Rantapää-Dahlqvist, Solbritt; Svenungsson, Elisabet; et al.
Abstract : Background: Lupus Nephritis (LN) is a cause of significant morbidity in SLE. While the genetic background to SLE has been well characterized, less is known about genes predisposing to LN. Methods: The study consisted of 2886 SLE patients, including 947 (33%) with LN. The discovery cohort (Sweden, n=1091) and replication cohort 1 (US, n=962) were genotyped on the Immunochip and replication cohort 2 (Norway/Denmark, n=833) on a custom array chip. Allele frequencies were compared between patients with LN and LN-negative patients. SNPs with a p-value <0.001 in the LN vs LN-negative analysis in the discovery cohort (nSNPs =139) were analyzed in replication cohort 1. Ten SNPs associated to LN (p<0.0002) in the discovery cohort were genotyped in replication cohort 2. A Bonferroni-corrected p-value of <1.0×10 -6 correcting for 48, 000 independent SNPs was considered significant. Results: In the discovery cohort, strong association to LN was found with several highly linked SNPs in BANK1, with the top signal in the intronic SNP rs4699261 (p=9.9×10 -5, OR 0.66). The association was also present in replication cohort 1 (p=9.5×10 -4 ). In a meta-analysis of the discovery and replication cohort 1, a total of 20 SNPs in BANK1 were associated to LN with the highest signal in rs4699261 (p=3.3×10 -7 ). There was a tendency towards association in replication cohort 2 (p=0.05) and in a meta-analysis of all cohorts, the association with BANK1 was strengthened (p=1.7×10 -7 ). Conclusion: BANK1 variations are associated with LN in patients with SLE. Upregulated BANK1 e xpression in renal biopsies from LN patients has previously been shown, however the exact role of BANK1 in LN pathogenesis remains to be elucidated.